The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1071/ah21056
|View full text |Cite
|
Sign up to set email alerts
|

Do people with multiple sclerosis receive appropriate support from the National Disability Insurance Scheme matching their level of disability? A description of disease ‘burden and societal cost in people with multiple sclerosis in Australia’ (BAC-MS)

Abstract: Objective. This study is the first to assess if the National Disability Insurance Scheme (NDIS) package allocated to people with multiple sclerosis (pwMS) is correlated with the disability level measured by standardised neurological assessment.Methods. We aimed to recruit 10 pwMS per expanded disability status score (EDSS) step, including EDSS 0 (no disability) up to 9 (bedridden), and requested information about their NDIS application. Value of their packages was compared with mobility, cognition and psycholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…As an observational study, a bias, based on disease severity and label indication, may have existed which could influence patient selection by the physician and risked recruiting a non-representative study sample. Although the mean age and gender demographics of the study cohort are similar to those reported in other real-world studies in Australia, 26 27 the baseline EDSS scores indicate a population with mild disease (85% with a baseline EDSS of 0–3). This is concordant with the treatment history which showed that 52% of the patients were treatment naïve and that the remainder had been switched to teriflunomide from a low efficacy agent.…”
Section: Discussionsupporting
confidence: 64%
“…As an observational study, a bias, based on disease severity and label indication, may have existed which could influence patient selection by the physician and risked recruiting a non-representative study sample. Although the mean age and gender demographics of the study cohort are similar to those reported in other real-world studies in Australia, 26 27 the baseline EDSS scores indicate a population with mild disease (85% with a baseline EDSS of 0–3). This is concordant with the treatment history which showed that 52% of the patients were treatment naïve and that the remainder had been switched to teriflunomide from a low efficacy agent.…”
Section: Discussionsupporting
confidence: 64%
“…The severity of disability in the MS patients was assessed based on the Expanded Disability Status Scale (EDSS), which evaluated pyramidal, cerebellar, brain stem, sensory, bowel and bladder, visual, and mental functions of patients (Şen, 2018). Patients with EDSS score 0 and 1 were considered without any disability and scores 4.5 and above were considered disabled (Lechner‐Scott et al., 2021).…”
Section: Methodsmentioning
confidence: 99%